Development of a SEIR Model with Two Optimal Controls for Infectious Disease Control: Computational Simulation Using MATLAB - Sitti Rosnafian Sumardi; Muhammad Hisyam (Universitas Islam Lamongan, 2026)
This study develops a Susceptible–Exposed–Infectious–Recovered (SEIR) mathematical model with two time-dependent optimal control strategies educational campaigns and medical treatment to analyze Ebola transmission. The nonlinear system is examined using Pontryagin’s Minimum Principle, and the optimality system is solved numerically through the Forward–Backward Sweep Method in MATLAB. Simulation results show that combined controls substantially reduce the peak number of infected individuals, decrease cumulative infection cases, and shorten the epidemic duration compared to the uncontrolled scenario. Early implementation of both interventions further improves epidemic suppression and reduces the overall cost functional value. These results demonstrate the effectiveness of integrated control strategies and highlight mathematical modeling as a decision-support tool in public health planning.